2018
DOI: 10.1111/hsc.12682
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and homelessness: A scoping review

Abstract: This paper reports the findings of a scoping review designed to identify research which has explored the relationship between cognitive impairment and homelessness. A systematic search of databases for articles published between 2007 and 2017 was conducted using keywords relating to cognitive impairments and homelessness. Sources were expanded using manual searches of citations and grey literature. Forty studies represented in 45 papers were selected for review using predefined inclusion criteria. Sources were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 55 publications
3
41
1
1
Order By: Relevance
“…For instance, as the time interval increases, people tend to smooth out the variation in alcohol consumed on each day and report less drinking overall (Hoeppner et al, 2010; Searles et al, 2002). Moreover, the TLFB’s accuracy can be influenced by a person’s impaired ability to recall alcohol consumption from memory, which may be more prevalent among people experiencing homelessness due to the high prevalence of comorbid mental and substance use disorders (Hurstak et al, 2017; Stasiewicz et al, 2008; Stone et al, 2019).…”
mentioning
confidence: 99%
“…For instance, as the time interval increases, people tend to smooth out the variation in alcohol consumed on each day and report less drinking overall (Hoeppner et al, 2010; Searles et al, 2002). Moreover, the TLFB’s accuracy can be influenced by a person’s impaired ability to recall alcohol consumption from memory, which may be more prevalent among people experiencing homelessness due to the high prevalence of comorbid mental and substance use disorders (Hurstak et al, 2017; Stasiewicz et al, 2008; Stone et al, 2019).…”
mentioning
confidence: 99%
“…This speculation is supported by the fact that only a minority of people who enter shelters in NYC have previously accessed available homelessness prevention services . Prior research has suggested high rates of traumatic brain injury and cognitive impairment among people who are homeless, which may have also been somewhat contributory to our findings, although we did exclude patients who were not able to understand the study informed consent process.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, disability is the umbrella term for impairments, activity limitations, and participation restrictions, referring to the negative aspects of the interaction between an individual (with a health condition) and that individual's contextual factors (environmental and personal factors) [8]. Many studies have reported that the prevalence of mental illness and physical and cognitive disability is higher among homeless individuals compared to the general population [9][10][11][12]. According to article 26 of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), which has been ratified and signed by the Irish government, all persons with a disability should have access to habilitation and rehabilitation [13].…”
Section: Introductionmentioning
confidence: 99%